2019
DOI: 10.21608/epsj.2019.29841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propolis and Zinc Methionine Supplementation on Improvement of Productive, Reproductive and Immunity Performance of Local Developed Insash Strain Under Egyptian Summer Conditions.

Abstract: The objective of this study was to evaluate the impact of propolis and zinc methionine (Zn-Met) supplementation on improvement of productive, reproductive and immunity performance of local developed Insash strain under Egyptian summer conditions. A total number of 180 laying hens and 36 cocks of Inshas chicken at 24 weeks of age was used and divided into equal 6 experimental groups (30 hens + 6 cocks), each of three replicates (10 hens +2 cock in each replicate). The obtained results revealed a significant (P<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Although there was no significant effect of protected methionine but it was slightly improvement in this semen characteristics in treatment group than control group. This results agree with Ezzat et al (2019) which found an un significant improvement in semen volume, concentration, individual motility but the researcher get un significant decrease in dead and total abnormal sperms in treatment group than control in male laying hens supplemented with zinc methionine than control group, also result in agreement with Nizza et al (2000) which found un significant effect of methionine supplementation on evaluations of for volume, concentration, and little variation in motility and live spermatozoa percentage. But the results in contrast with Hong et al (2018) which found a significant effect of methionine supplementation in ration on semen concentration, individual motility, live sperms and significant decreased in abnormal sperms percentage on boar, also our results contrast with El-Sharawy et al (2012) which he found a significant effect of drenched zinc methionine on semen parameters of crossbred Rams.…”
Section: Resultssupporting
confidence: 87%
“…Although there was no significant effect of protected methionine but it was slightly improvement in this semen characteristics in treatment group than control group. This results agree with Ezzat et al (2019) which found an un significant improvement in semen volume, concentration, individual motility but the researcher get un significant decrease in dead and total abnormal sperms in treatment group than control in male laying hens supplemented with zinc methionine than control group, also result in agreement with Nizza et al (2000) which found un significant effect of methionine supplementation on evaluations of for volume, concentration, and little variation in motility and live spermatozoa percentage. But the results in contrast with Hong et al (2018) which found a significant effect of methionine supplementation in ration on semen concentration, individual motility, live sperms and significant decreased in abnormal sperms percentage on boar, also our results contrast with El-Sharawy et al (2012) which he found a significant effect of drenched zinc methionine on semen parameters of crossbred Rams.…”
Section: Resultssupporting
confidence: 87%
“… Khairani et al (2016) clarified that the eggshell weight and thickness were unaffected by the addition of choline to diets with various levels of methionine, whereas previous authors pointed out an increase in the eggshell thickness ( Jalal and Al-Neemi, 2017 ) and eggshell relative weight ( Kiran et al, 2013 ; Jalal and Al-Neemi, 2017 ) when choline was added. For betaine, Sadegheymojarad et al (2018) in quails and Ezzat et al (2011) in hens noted that the addition of betaine did not affect eggshell parameters. Park and Ryu (2011) observed that adding betaine to diets containing various levels of methionine did not affect the eggshell-breaking strength and eggshell thickness in laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…Ratriyanto et al [35] reported increased crude protein and fiber digestibility at 0.06% and 0.12% doses. The dietary addition of betaine improved the digestion of crude protein and ether extract in laying chickens [36]. Increased digestibility of crude protein, crude fiber, and ether extract may have contributed to the increased body weight gain in groups PC and T1.…”
Section: Growth Performancementioning
confidence: 94%